Impact of centrifugation on thrombin generation in healthy subjects and in patients treated with direct oral anticoagulants. (12th July 2021) - Hardy, Michael; Dellanoce, Claudia; Douxfils, Jonathan; Carlo, Audrey; Lessire, Sarah; Bouvy, Céline; Testa, Sophie; Mullier, François
Abstract: Introduction: Double centrifugation before freezing is recommended before thrombin generation assays (TGA). However, this procedure is not mandatory for routine hemostasis tests, precluding the use of these samples for TGA. The aim of this study is to assess the impact of single and double centrifugation on TGA performed on frozen samples from healthy volunteers (HVs) and patients receiving direct oral anticoagulants (DOACs). Methods: Forty HVs and 57 patients receiving a DOAC (dabigatran, rivaroxaban, apixaban, or edoxaban) were included in this prospective double‐center observational study. Blood was collected into 109 mmol/L citrated tubes and frozen at −70°C before TGA using ST Genesia with STG‐DrugScreen reagent. Four pre‐analytical conditions were studied: (A) single centrifugation (2000 g, 15 minutes) before freezing; (B) one centrifugation before freezing and another after thawing (2000 g, 15 minutes for both); (C) one centrifugation before freezing(2000 g, 15 minutes) and another after thawing (2000 g, 10 minutes); (D) double centrifugation (2000 g, 15 minutes) before freezing (reference). Centrifugation conditions (A), (B), and (C) were compared with the reference condition (D). Acceptable relative differences were defined at 6%, 8%, and 10% for normalized lag time, endogenous thrombin potential, and peak height, respectively. Results: Centrifugation conditions had a small but acceptable impact on HVs samples, but single centrifugation always resulted in unacceptable reductions in normalized lag times for DOAC samples. A second centrifugation after thawing permitted the recovery of acceptable differences for the three TGA parameters for edoxaban but not for apixaban, rivaroxaban, nor dabigatran. Conclusion: Double centrifugation before freezing should remain the recommended pre‐analytical condition before TGA.